EDUKASI KARAKTER YANG INOVATIF (Studi Tentang Kepribadian Muslim yang Toleran) - Arif, Mohammad (PERMANA, 2015)
Education is an organization of the most fundamental in determining the life and future of a nation . Thus, in the process should be able to adjust to the conditions of the times. Education is very important to create a society berpedaban . Civilization of a nation will be added and the birth of an education system that is used by the nation. A civilized society , are educated people .According to Muhammad Naqib Al - Attas , Islamic education was more appropriately termed at- tadib ( compared tarbiyah term , study groups and other) because the concept of education tadib give adab / culture . Education takes place with a focus on the human being as subject and object , in order to meet the intellectual and spiritual potential . Along with rapid technological progress , automatically requires innovation in the field of education.Education is no longer enough organized traditionally , it flow without a clear target , and the absence of procedures for reaching a target that proved to be effective and efficient . If we retain the traditional ways without convening innovation , then obviously the Muslims and Islamic education will fall further behind in all aspects . For this reason the need for innovation in Islamic education is meant to be born Islamic education quality and competitive. Educational / character education is